Dividend announcements and stock market reaction - Jais, Mohamad; Abdul Karim, Bakri; Funaoka, Kenta; Zainol Abidin, Azlan (2009)
This paper examines the effect of dividend Announcements on stock market reaction in Kuala Lumpur Stock Exchange. Using an event study approach, the evidence shows that dividend increase announcements are greeted positively by investors, while there are some evidences suggesting investors react negatively prior to dividend decrease announcements. The observations are then separated into the magnitude of dividend change and income change. This paper also separates the observations into government linked companies (GLCs) and non-GLCs.